1997
DOI: 10.1007/s004390050532
|View full text |Cite
|
Sign up to set email alerts
|

Adult onset globoid cell leukodystrophy (Krabbe disease): analysis of galactosylceramidase cDNA from four Japanese patients

Abstract: We examined galactosylceramidase (GALC) cDNA in four Japanese patients with adult onset globoid cell leukodystrophy (Krabbe disease; AO-GLD) by polymerase chain reaction/single-strand conformation polymorphism (PCR-SSCP) analysis, subsequent sequence determination, and restriction enzyme digestion of PCR products, initial symptoms were the onset of slowly progressive spastic paraplegia from the middle of the second decade, and all patients had diminished GALC activity in their leukocytes. We identified three m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 24 publications
(47 reference statements)
4
40
1
Order By: Relevance
“…Mutations have been identified in the GALC gene that affect gene splicing and mRNA stability or cause deletions, frameshifts, and missense mutations (5,(13)(14)(15)(29)(30)(31)(32)(33)(34). A large proportion of the missense mutations in GALC that cause Krabbe disease are likely to result in protein mistargeting or premature degradation (33).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations have been identified in the GALC gene that affect gene splicing and mRNA stability or cause deletions, frameshifts, and missense mutations (5,(13)(14)(15)(29)(30)(31)(32)(33)(34). A large proportion of the missense mutations in GALC that cause Krabbe disease are likely to result in protein mistargeting or premature degradation (33).…”
Section: Discussionmentioning
confidence: 99%
“…Functional studies would be necessary to determine whether p.V320M and others (such as p.D94=) are indeed pseudodeficiency alleles. p.L618S was found in cis with several other variants in our population (Supplementary Table S3 online), and those who carried two copies of p.L618S were categorized as being at high (1; case 9, 3,28,29,32 Nearly all of the 348 infants referred carried at least one of the three common activity-attenuating polymorphisms (p.R168C, p.D232N, p.I546T). The frequency of each was elevated in the referral population compared with published data.…”
Section: Genotypes and Phenotypesmentioning
confidence: 99%
“…Whereas several papers (Tatsumi et al 1995;Furuya et al 1997;Kukita et al 1997-98;Satoh et al 1997;Fu et al 1999) have reported Krabbe disease mutations in Japanese patients, clear genotype-phenotype correlations remain obscure, because of the small number of subjects studied. We evaluated the GALC gene in 17 Japanese patients, classifying mutations according to clinical phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…1a). I66M+I289V, first reported by Furuya et al (1997), is a unique mutation identified in the Japanese population. Only when two single-nucleotide substitutions (I66M, I289V) resided on the same allele was their combination (I66M+I289V) proved to be a pathogenic mutation .…”
Section: Patientsmentioning
confidence: 99%